CIRCULATORY AUTOANTIBODIES AGAINST HYALURONIC ACID BINDING PROTEINS: A NOVEL SERUM BIOMARKER - Nunna, Venkatrao; SD, Banerjee; M, Karuna Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Background: Circulating autoantibodies have been extensively investigated as possible markers for early diagnosis of cancer. The present study was carried out to investigate whether anti-HABPs autoantibodies could be classified as a serum biomarker for malignant tumors. Methods: An enzyme-linked immunosorbent assay, western blot was used to detect anti-HABPs autoantibodies in sera from 99 patients with various types of cancers and 50 healthy subjects matched by age and gender. Result: Our results clearly indicated that patients with cancer have significant higher circulating levels of anti-HABPs antibodies as compared to control subjects (ð‘ƒ < 0.001). Receiver operating characteristic plot test has exhibited 91.9% sensitivity and 76.3% specificity. Conclusion: anti-HABPs autoantibodies are promising biomarker for malignant tumors and could play a role in the development of multimarker assay for the early detection of cancer